Vaksin Gumboro Menyebabkan Imunosupresif pada Respons Primer Vaksin Penyakit Tetelo Ayam Pedaging - Kencana, Gusti Ayu Yuniati; Adi, Anak Agung Ayu Mirah; Ardana, Ida Bagus Komang; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2012)
The variety of Gumboro live vaccine strains (hot, intermediate, and mild) are available inIndonesia. The immunosuppresive effect of these vaccines under field conditions is not known.This research was conducted to determine this devastating effect of such vaccine strains on theimmune response of chickens vaccinated againts Newcastle disease (ND). Sixty chickens werekept separately in five groups (i.e. V1, V2, V3, V4, and K). At the age of seven days, group V1, V2,and V3 were given hot, intermediate, and mild strains of Gumboro live vaccine respectively whilethe other two groups recieved no Gumboro vaccine (V4 and K). At the age of 14 days, all groups,except group K which were kept as a negative control, were vaccinated against ND. The level ofantibody produced in response to ND vaccination was measured in sera collected at day 0, 7, 14,and 21 post ND vaccination using a standard micro-haemaglutination inhibition test. Data of theantibody titers were analyzed using analysis of variance followed by Duncan’s multiple range test.The results showed that all Gumboro vaccine strains still retain its immunosuppressive nature onhumoral immune response in chickens that later vaccinated against ND. The geometric meantiter (GMT) of anti-NDV antibody of group V4 (unvaccinated againts Gumboro) was significantlyhigher than that of group V1, V2, and V3, i.e. groups of chickens that had been given varietystrains of Gumboro vaccines, at the first and second week after ND vaccination (p<0.05). Thedifference of this immunosuppressivenes among variety of Gumboro vaccine strains need furtherclarification.
Keywords: Gumboro vaccines, immunosuppresive effect, immune response, ND vaccine, broiler chickens